An effective disinfection protocol for contamination control in vitro establishment of Mortiño (Vaccinium floribundum Kunth) and identification of endogenous microbes (Scientia Agropecuaria, 2025)
The Vaccinium genus consists of a variety of berries with high nutritious components consumed worldwide leading to the development of micropropagation protocols to supply the demand. Mortiño, the Andean Blueberry (Vaccinium floribundum Kunth) is a wild berry that grows in high-altitude grasslands with nutritious and commercial potential in Ecuador. In this study, the use of PPMTM (Plant Preservative Mixture™) was effective controlling contamination for the in vitro establishment of Vaccinium floribundum Kunth in contrast to a conventional method using EtOH and Clorox. Stems were defoliated and cut into 1 cm segments, then immersed in liquid MS (Murashige & Skoog) supplemented with 5% v/v PPMTM without pH adjustment for 5 hours under constant shaking. After immersion, segments were transferred to flasks containing WPM (Woody Plant Media) medium supplemented with an additional 2 mlL-1 PPMTM. Persistent microbial contaminants in the in vitro explants were isolated and identified through molecular methods and gene sequences analyzed using the GenBank database resulted in the identification of three bacterial species: Methylobacterium sp., Methylobacterium radiotolerans, and Bacillus pumilus. In addition, three fungal species were also discovered: Xylaria sp., Xylaria feejeensis, and Diaporthe lutecens. Additionally, a multiplication assay was made with the aseptic stems from the sterilization protocol to evaluate four different growth regulators: 2ip, kinetin, zeatin and meta-topolin. kinetin showed very low responses with a mean of 1.2 shoots per stem. The highest number of shoots per stem (9 shoots) was obtained with 5 mg L-1 2ip. The use of zeatin and meta-topolin facilitated shoot proliferation with the following concentrations: 3 mg L-1 zeatin + 0.5 mg L-1 NAA (1-Naphthaleneacetic Acid) and 3 mg L-1 Meta-topolin + 0.5 mg L-1 NAA. These findings demonstrate the successful establishment of an in vitro disinfection and multiplication protocol for V. floribundum.
Keywords: Vaccinium floribundum Kunth; micropropagation; endogenous contamination; Mortiño; Andean blueberry